Examining the win‐win proposition of shared value across contexts: Implications for future application. (4th September 2017) - Voltan, Annika; Hervieux, Chantal; Mills, Albert
Abstract: This article examines the concept of creating shared value (CSV) as articulated by Michael Porter and Mark Kramer, in non‐Western and Western contexts. We define non‐Western contexts as those in so‐called "developing" countries and emerging economies, whereas Western ones pertain to dominant thinking in "developed" regions. We frame our research in postcolonial theory and offer an overview of existing critiques of CSV. We conduct a critical discourse analysis of 66 articles to identify how CSV is being cited by authors, and potential underlying power dynamics that affect its relevance for non‐Western contexts. Our review exposes increasingly critical views about the paradoxical positioning of CSV as an instrumental concept that can offer "win‐win" solutions, particularly from those working in non‐Western settings. Western perspectives generally tend to be more supportive of its instrumental nature, but also recognize the increasing complexity of the business‐society nexus and stakeholder engagement. We argue that the CSV framework requires further development to maintain credibility and applicability, especially in non‐Western domains.